2014
DOI: 10.1073/pnas.1317502111
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptive scientific narratives for communicating usable science

Abstract: In this paper I describe how a narrative approach to science communication may help audiences to more fully understand how science is relevant to their own lives and behaviors. The use of prescriptive scientific narrative can help to overcome challenges specific to scientific concepts, especially the need to reconsider long-held beliefs in the face of new empirical findings. Narrative can captivate the audience, driving anticipation for plot resolution, thus becoming a self-motivating vehicle for information d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 56 publications
0
69
0
2
Order By: Relevance
“…Videos and games are scalable training methods that can be used for efficient teaching of cognitive skills (e.g., Downs, 2014;Haferkamp, Kraemer, Linehan, & Schembri, 2011;Sliney & Murphy, 2008). The experiments, funded by Intelligence Advanced Research Projects Activity BAA-11-03, tested whether debiasing training could produce persistent reductions in six cognitive biases identified by our program sponsor as affecting all types of intelligence analysis.…”
Section: Persistent Debiasing With a Single Interventionmentioning
confidence: 99%
“…Videos and games are scalable training methods that can be used for efficient teaching of cognitive skills (e.g., Downs, 2014;Haferkamp, Kraemer, Linehan, & Schembri, 2011;Sliney & Murphy, 2008). The experiments, funded by Intelligence Advanced Research Projects Activity BAA-11-03, tested whether debiasing training could produce persistent reductions in six cognitive biases identified by our program sponsor as affecting all types of intelligence analysis.…”
Section: Persistent Debiasing With a Single Interventionmentioning
confidence: 99%
“…10 Pediatric providers can teach parents and teens to think of sexual behaviors along a continuum from “less risky” to “very risky” and encourage parents to suggest ways to achieve sexual pleasure with a partner that involve less risk than intercourse, such as hugging, kissing, mutual masturbation, and oral sex. Some parents may balk at the idea of encouraging these “less risky” behaviors, but providing them with a more nuanced understanding of risk minimization strategies can protect their teen’s health.…”
Section: Introductionmentioning
confidence: 99%
“…They can explain in detail how something works, summarizing large amounts of content in a way that is difficult through text or static photos 12 . Videos have also been shown to improve learning outcomes, 13 and can be enhanced through the use of narratives 14 . Research has shown that dramatized video increases viewer identification with characters, thus driving narrative engagement and the creation of episodic memories - which improves memory recall.…”
Section: Digital Opportunitiesmentioning
confidence: 99%